RISK ANALYSIS OF SHARIA STOCKS IN THE INFRASTRUCTURE, UTILITIES AND TRANSPORTATION SECTOR LISTED ON THE JAKARTA ISLAMIC INDEX (JII) 2015-2023 - Akbar AA, Malik; Syam, Muhammad; Fathoni, Hamdan (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
This research is intended to analyze the risk comparison using the Value at Risk (VaR) Variance Covariance and Value at Risk (VaR) Historical Simulation models in the Infrastructure, Utilities and Transportation subsectors. The development of infrastructure, utilities, and transportation plays a very important role in national development and is the main driver of regional growth and the industrial sector. Improvements in the regulatory and investment policy framework are expected to significantly increase the availability of infrastructure facilities and services. The population involved in this study includes 9 companies listed in the JII in the Infrastructure, Utilities, and Transportation sector, which are used as samples. The data used is secondary data obtained from www.yahoo.finance.com. Data analysis was carried out using a two-sample average test. The test results of the Value at Risk (VaR) Historical Simulation and Variance Covariance values are largest in INDX stocks, followed by other stocks, and those with the lowest risk level are TLKM stocks for the upcoming 5-day, 7-day, and 15-day periods with good values for alpha 1%, 5%, and 10%. The results concluded that the comparison between VaR Variance Covariance and VaR Historical Simulation produces a good level of risk and helps in determining sectors that are worth investing in the future, and can describe the fundamental strength of each sector.